Training of Rice Farmers and Its Effect on Socio-Economic Assets Acquisition and Change in Status - Issahaku, Adams; Obeng, Francis K.; Akudugu, Aboko; Yeboah, Richard W. N. (Business Management and Strategy, 2022)
Training programmes for rice farmers is believed to be an activity leading to the improvement in yield if it is well managed and implemented. Japan International Corporation Agency (JICA) initiated a training programme for rice farmers in three regions in Northern Ghana. Indeed, the benefits of training could be social, cognitive, economic or both. The training was intended to help increase rice farmers yield leading to productivity and profitability. This study was set up to evaluate the extent to which the rainfed lowland rice training programme influenced changes and improvement in socio-economic status of the rice farmers. A sample of 257 out of the total population of 880 was selected across both sex for this study. The analysis showed that all participants in the training benefitted in the form of changes in their socio-economic statuses as well as cognitive improvement. Various assets were acquired from proceeds of excess rice sole after feeding their families. One asset the majority of the farmers acquired was cell phone with all the women farmers acquiring cooking utensils either for their domestic use or in preparation towards settling their daughters when they are due for marriage. It was established that the rice training programme was beneficial to farmers and therefore should be extended to cover all rice farmers in the three regions in particular and to rice farmers in Ghana in general.